Surveillance Bias in Cancer Risk After Unrelated Medical Conditions: Example Urolithiasis - Kari Hemminki (Nature Portfolio, 2017)
Abstract We analysed cancer risks in patients with urinary tract stones but some features of the generated results alarmed us about possible surveillance bias, which we describe in this report. We used nationwide Swedish hospital records to identify patients with urinary tract stones (N = 211,718) and cancer registration data for cancer patients for years 1987 to 2012. Standardized incidence ratios (SIRs) for cancer were calculated after the last medical contact for urinary tract stones. All cancers were increased after kidney (SIR 1.54, 95%CI: 1.50–1.58), ureter (1.44, 1.42–1.47), mixed (1.51, 1.44–1.58) and bladder stones (1.63, 1.57–1.70). The risk of kidney cancer was increased most of all cancers after kidney, ureter and mixed stones while bladder cancer was increased most after bladder stones. All SIRs decreased steeply in the course of follow-up time. Tumour sizes were smaller in kidney cancer and in situ colon cancers were more common in patients diagnosed after urinary tract stones compared to all patients. The results suggest that surveillance bias influenced the result which somewhat surprisingly appeared to extend past 10 years of follow-up and include cancers at distant anatomical sites. Surveillance bias may be difficult to avoid in the present type of observational studies in clinical settings.